Inflation and Benefits under the U.S. Old Age, Survivors and Disability Insurance - Neil Swan (Queen's University, Department of Economics, 1969)
The aim of this paper is to estimate under limits on the loss from inflation for a typical OASDI (Old-age,Survivors and Disability/Insurance) beneficiary and thus to show that for the majority of old-age pensioners in the United States protection against inflation is quite good. Moreover, the protection is not fortuitous, but a necessary consequence of the way benefits are set.
Keywords: 330